Imaging characteristics of liver metastasis from gastrointestinal stromal tumor before and after imatinib mesylate treatment - Şerife ULUSAN; Zafer KOÇ; Fazilet KAYASELÇUK (Turkish Journal of Gastroenterology, 2019)
-